Analisis Naratif: Sebuah Metode Kristiani Hermeneutika Kitab Suci - Tarmedi, P. A. Didi (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2013)
Most of the content of the Scriptures are conveyed in narratives telling God’s acts of salvation. The communication of the narratives in a vigorous way can give weight to faith confession, liturgy, and catchesis. Christian faith proclamation is basically a series of narratives telling the story of life, death, and resurrection of Christ as has been told by the Scriptures and retold in narratives. A ‘narrative analysis’ is a method that has its advantages on the ‘narrative world’ with all the images and imagination. By entering the narrative world constructed by the authors of the Scriptures, the reader participates in the ‘world of images’ presenting the meanings contained in it and that brings a useful faculty for the contextual praxis of proclamation. This model of communication places the author and the reader in the same ‘narrative world’ though with different experiences. A narrative analysis is not so much a ‘door’ opening to the past behind the narratives as a ‘mirror’ projecting particular images, i.e. the narrative world, so as to provide an ability to the reader to absorb the meanings conveyed in the narratives and to experience their saving power.